DETERMINASI PELANGGAN BERKUNJUNG KEMBALI PADA POLIKLINIK EKSEKUTIF NUSA INDAH RSUD TUGUREJO SEMARANG - Aditya Nugraha; Naili Farida; Septo Pawelas Arso (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
The hospital is a health service unit for the community, a complete health service that provides inpatient, outpatient and emergency services. The research objective was to determine and analyze the effect of brand image and service quality on customer loyalty through customer value and intention to return to the Nusa Indah Executive Polyclinic, Tugurejo Hospital, Semarang City. Methodology of  this research was a quantitative analytic observational study. The research subjects were patients who were treated at the outpatient installation of the Nusa Indah Executive Polyclinic, Tugurejo Hospital, Semarang City. The results showed First, the quality of service has an effect on customer value at the executive polyclinic of RSUD Tugurejo Semarang. Second, the results obtained that brand image has a positive effect on customer value at the Nusa Indah executive polyclinic, Tugurejo Hospital, Semarang. Third, the results showed that customer value had a positive effect on the interest in repeat visits at the Nusa Indah executive polyclinic, Tugurejo Hospital, Semarang. Fourth, the results showed that customer value had a positive effect on customer loyalty at the Nusa Indah Executive Polyclinic, Tugurejo Hospital, Semarang. Fifth, the results of the intention to revisit have a positive effect on loyalty. In sum, service quality and brand image assessed by customers (patients) are very good so that they have an interest in revisiting for treatment if they are sick, this is a form of patient loyalty to the Nusa Indah executive polyclinic, Tugurejo Hospital Semarang.keywords:  service quality, customer value, brand image, repeat interest, customer loyaltyRumah Sakit merupakan unit pelayanan kesehatan bagi masyarakat, pelayanan kesehatan secara paripurna yang menyediakan pelayanan rawat inap, rawat jalan dan gawat darurat.   Tujuan penelitian adalah untuk mengetahui dan menganalisis pengaruh citra merek dan kualitas layanan terhadap loyalitas pelanggan melalui nilai pelanggan dan niat berkunjung kembali di Poliklinik Eksekutif Nusa Indah RSUD Tugurejo Kota Semarang. Metode penelitian ini merupakan penelitian observasional analitik kuantitatif. Subyek penelitian adalah pasien yang berobat di instalasi rawat jalan Poliklinik Eksekutif Nusa Indah RSUD Tugurejo Kota Semarang. Hasil yang didapatkan, pertama didapatkan kualitas layanan berpengaruh terhadap nilai pelanggan di poliklinik eksekutif RSUD Tugurejo Semarang.  Kedua didapatkan hasil citra merek berpengaruh positif terhadap nilai pelanggan di poliklinik eksekutif Nusa Indah RSUD Tugurejo Semarang. Ketiga didapatkan hasil nilai pelanggan berpengaruh positif terhadap minat kunjungan ulang di poliklinik eksekutif  Nusa Indah RSUD Tugurejo Semarang. Keempat didapatkan hasil nilai pelanggan berpengaruh positif terhadap loyalitas pelanggan di poliklinik eksekutif nusa indah RSUD Tugurejo Semarang. Kelima didapatkan hasil niat berkunjung kembali berpengaruh positif terhadap loyalitas. Kualitas layanan dan citra merek dinilai pelanggan (pasien) sangat baik sehingga mereka mempunyai minat kunjungan ulang untuk berobat jika sakit, hal ini sebagai wujud loyalitas pasien ke poliklinik eksekutif Nusa Indah RSUD Tugurejo Semarang.Katakunci: kualitas layanan, nilai pelanggan, citra merek, minat kunjungan ulang, loyalitas pelanggan